Plataforma de Jogos Playkids - Gomes, Lucas Cidade dos Santos (ICET - Instituto de Ciências Exatas e Tecnologia (Itacoatiara), 2022)
Digital games are available at all school levels, from kindergarten, in which play and games become common activities of children's nature, to the various subjects in higher education courses, being widely used in simulations of real environments to the practice and learning of content. The creation of recreational games for the industry has grown exponentially, taking into account the importance of teaching through education in all forms. Therefore, the present work aims to present the PlayKids platform in which it allows its users to have access to games intended for the education of children between 5 and 12 years old. The platform was based on information obtained from documentary research and developed using the spiral model in conjunction with various software technologies. After the construction, an evaluation was carried out through a questionnaire with scales based on the Technological Acceptance Model, in which the results obtained highlighted positive aspects about the ease of use and usefulness of the application.